As habitações da etnia Kawaiweté/Kaiabi como temática de material didático para promover aprendizagens no ensino médio - Oliveira, Leilane Alves de (2022)
The present study presents an investigation about the elaboration and use of didactic material with the theme dwellings of the indigenous people of the Kaiabi ethnicity from villages in the Lower Xingu region, in order to favor the learning of scientific, social and cultural contents by high school students. Working on science teaching concepts related to the knowledge and practices of indigenous peoples can enable better science learning and contribute to the rescue and knowledge of the culture of indigenous peoples, to overcome prejudice and discrimination against these peoples. This investigation was developed in the following stages: elaboration of the didactic material, a booklet, and its use in the classroom. The elaboration of the didactic material was made from information obtained in an online interview with non-indigenous members of the Vale do Arinos Museum, located in the municipality of Juara, MT. In this interview, it was possible to know the plant resources used by the indigenous people in the construction of their houses and the construction methods. The interview allowed a better understanding of indigenous dwellings and the production of a booklet on the Kaiabi culture relating indigenous knowledge with Natural Sciences. After the elaboration of the teaching material, it was used and validated in pedagogical actions in a public school in Sinop/MT, in partnership with a high school teacher of Natural Sciences. The teacher used the logbook to record her perceptions of the students' learning and answered forms in order to evaluate the technical and pedagogical aspects of the teaching material. From the analysis of the forms and the logbook, it was possible to conclude that the booklet entitled Habitações Indígenas e o Ensino de Ciências da Natureza helps teachers to work on concepts of Natural Sciences related to the history of indigenous peoples in which it allows a greater understanding content and helped students learn to discuss relevant issues in our current society.